Characterization of new sources of resistance to African strains of Xanthomonas oryzae pv. oryzae, agent bacterial leaf blight of rice - (:unkn) unknown (My University, 2022)
Bacterial Leaf Blight (BLB), caused by the Gram-negative bacterium Xanthomonas oryzae pv. oryzae (Xoo), is one of the most devastating diseases of rice in West Africa and Asia. Xoo injects through its type-III secretion system a full cocktail of TAL ("Transcription Activator-Like") effectors into the host plant cell. By means of their nuclear localization signals (NLS) TALEs are next imported into the host nucleus where they bind through central tandem repeats to host promoter targets at a sequence called EBE ("Effector Binding Element"), with the final aim of initiating gene transcription thanks to their activation domain (AD). Xoo is thus able to modulate the expression of plant genes by hijacking the plant transcriptional machinery and induce so-called susceptibility (S) genes that favor the development of the bacterium and disease consequently. In some cases, TALEs can activate so-called executor (E) genes whose expression leads to plant defense reactions and results in resistance. Genetic diversity analyses have shown that Xoo is comprised of two lineages that corresponding to strains from Africa for one and Asian strains for the other. African and Asian Xoo differ in their number of tal genes, but also in the type of resistance they elicit. Noteworthy, none of the races identified in Africa have been found in Asia.The objective of this thesis was to identify sources of resistance in rice in order to provide new strategies for the control of BLB in Africa. In a gain-of-function approach, preliminary analyses identified several TALEs of the Malian strain MAI1 with potential avirulence activity on the rice varieties IR64, CT13432 and FKR47N. To further confirm these results, a loss-of-function approach was undertaken, consisting in the inoculation of a library of BAI3Δtal mutants deriving from the Xoo Burkinabe strain BAI3, whose TALome (tal genes repertoire) is very similar to that of MAI1, on each of the three resistant varieties. This work valid
Keywords: African Research